Measuring Progress and Projecting Attainment on the Basis of Past Trends of the Health-related Sustainable Development Goals in 188 Countries: An Analysis From the Global Burden of Disease Study 2016 - Feigin, V; GBD 2016 SDG Collaborators (Elsevier, 2017)
No abstract.